Textbook of pediatrics - Mathur, GP; Mathur, Sarla (CBS Publishers & Distributors Pvt Ltd, 2015)
Unique features of this edition are Emphasis on recognition and management of common pediatric conditions, Comprehensive tables and boxes highlighting important differential diagnosis and management, Important issues such as sex education, medical ethics, legal issues in pediatric practice, and guiding pediatricians in child care are discussed